Myrrh protects against IL-13-induced epithelial barrier breakdown in HT-29/B6 cells - Hader, Helena; Hering, Nina A.; Schulzke, Jörg-Dieter; Bücker, Roland; Rosenthal, Rita (Frontiers in Pharmacology, 2023)
The oleoresin myrrh has been used for centuries as an anti-inflammatory remedy for a variety of diseases and is said to have a protective effect on the intestinal epithelium. An intact epithelial barrier function is the prerequisite for a healthy gut. Inflammatory and infectious diseases of the intestine, in particular, lead to barrier impairment resulting in leak-flux diarrhea and mucosal immune responses. Therefore, the aim of the present study was to investigate the protective effect of myrrh in an experimental inflammatory situation, namely under the influence of IL-13, one of the key cytokines in ulcerative colitis. We used human intestinal epithelial HT-29/B6 cell monolayers for functional and molecular assessment of the epithelial barrier under IL-13 and myrrh treatment. IL-13 induced a loss in barrier function that was fully restored with myrrh treatment, as shown by transepithelial electrical resistance measurements. The molecular correlate of the IL-13-mediated barrier dysfunction could be assigned to an upregulation of the channel-forming tight junction (TJ) protein claudin-2 and to a subcellular redistribution of the TJ protein tricellulin, loosening the sealing of tricellular TJs. Moreover, IL-13 exposure leads to an increase in the number of apoptotic cells, contributing to the leak pathway of barrier dysfunction. Myrrh protected against changes in TJ deregulation and decreased the elevated apoptotic ratio under IL-13. The protective effects are mediated through the inhibition of the STAT3 and STAT6 pathway.In conclusion, our results demonstrate that myrrh exhibits antagonizing effects against IL-13-induced barrier impairment in a human intestinal cell model. These data suggest the use of myrrh as a promising option in the treatment of inflammatory bowel disease.